(untitled) (Ozone Therapy Global Journal, 2016)
While the therapeutic approach to cancer is complicated, it becomes a challenge for clinicians. The aim of this study was the use of ozone therapy in four oncology canine patients and the assessment of results related to the quality of life and survival thereof. We did not obviate the concomitant use of conventional treatments. Animals belonging to the following breeds: crossbred Mastiff. Mastiff. Golden Retriever and crossbred German Shepherd, were diagnosed with different types of tumours (Lymphosarcoma, Chondrosarcoma, Adenocarcinoma and Osteosarcoma, respectively). Ozone therapy was applied in treatment cycles rectally, by autohaemotherapy and by local infiltration. Concomitant use of ozone improved the quality of life and increased survival of the animals in all cases.